Self-assembly of well-ordered whisker-like manganese oxide arrays on carbon fiber paper and its application as electrode material for supercapacitors - Luo, Yongsong (2013)
Self-assembled well-ordered whisker-like manganese dioxide (MnO2) arrays on carbon fiber paper (MOWAs) were synthesized via a simple in situ redox replacement reaction between potassium permanganate (KMnO4) and carbon fiber paper (CFP) without any other oxidant or reductant addition. The CFP serves as not only a sacrificial reductant and converts aqueous permanganate (MnO4−) to insoluble MnO2 in this reaction, but also a substrate material and guarantees MnO2 deposition on the surface. The electrochemical properties were examined by cyclic voltammograms (CV), galvanostatic charge/discharge, and electrochemical impedance spectroscopy (EIS) in a three-electrode cell. According to the CV results, the ordered MOWAs yield high-capacitance performance with specific capacitance up to 274.1 F g−1 and excellent long cycle-life property with 95% of its specific capacitance kept after 5000 cycles at the current density of 0.1 A g−1. The high-performance hybrid composites result from a synergistic effect of large surface area and high degree of ordering of the ultrathin layer of MnO2 nanowhisker arrays, combined with the flexible CFP substrate and can offer great promise in large-scale energy storage device applications.